Privatizing the commons: New approaches need broader evaluative criteria for sustainability. Issue 1 (April 2019) - Partelow, Stefan; Abson, David J.; Schlüter, Achim; Fernández-Giménez, María; von Wehrden, Henrik; Collier, Neil
Privatization is, since Hardin, often promoted as a solution to many natural resource management challenges, particularly in common-pool resource systems. However, novel forms of privatization are being implemented in unexamined ways. In this article we explore how privatization affects natural resource management from the perspective of multi-dimensional social-ecological systems. We critique the notion that privatization is desirable due to its pure efficiency, and argue that efficiency must be relative to achieving other normative societal goals, in particular, sustainability. While sustainability outcomes often cannot be fully actualized, the processes through which privatization attempts to achieve them are more tangible criteria. First, we draw on (1) distributional and (2) procedural justice as normative societal goals to assess effectiveness of different forms of privatization. Second, we analyze the broader implications of privatization for social-ecological system functioning considering (3) path dependency and (4) spillover effects. We apply these four concepts to examine three different cases of privatization: eco-certification in fisheries, seed patents in agriculture and property rights in rangelands. We argue that the evaluative criteria for the success of privatization are often oversimplified, and highlight how privatization can influence social-ecological systems and the achievement of normative goals in largely unexamined ways.